Bamboo Leaf Flavonoids Extracts Alleviate Oxidative Stress in HepG2 Cells via Naturally Modulating Reactive Oxygen Species Production and Nrf2‐Mediated Antioxidant Defense Responses. Issue 6 (22nd May 2019) - Yu, Yue; Li, Zhanming; Cao, Guangtian; Huang, Shudan; Yang, Hongshun
Abstract : Abstract: In this study, bamboo leaf flavonoids extracts (BFE) were employed to alleviate oxidative stress induced by oleic acid in HepG2 cells. Biochemical indexes, intracellular reactive oxygen species production, lipid droplets accumulation, antioxidant enzymes production, and mitochondrial membrane potential were determined to show the alleviation performance of BFE intervention ( P < 0.05). Importantly, the results of qRT‐PCR and western blot determination indicated that BFE intervention upregulated the expression of Nrf2/HO‐1/NQO1 to initiate the antioxidant defense response for counteracting oxidative stress ( P < 0.05). Moreover, mitochondrial membrane potential–mediated apoptosis and FOXO signaling pathway initiation caused by BFE intervention may together contribute to oxidative stress alleviation in HepG2 cells. In conclusion, these findings suggested that BFE intervention upregulated related antioxidant defense responses for preventing cells from oxidative damage. Practical Application: In this study, bamboo leaf flavonoids extracts intervention upregulated related antioxidant defense responses for preventing cells from oxidative damage. These findings in bamboo leaf extracts antioxidants are a promising and innovative subject with practical applications to enhance the development of bamboo leaf extracts functional products in the food industry.